AI and Justice: Is Uzbekistan’s Judiciary system prepared? - Sojida Murodova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The advancing transformation of legal systems by artificial intelligence (AI) worldwide leads to questions about its possible implementation in developing country judiciaries as there are no international regulations addressing AI by international organizations like the United Nations or International Court of Justice. In this case, every country whether developed or developing is making an effort to deal with this trend according to its own national legislature system. This paper investigates how ready the judicial system of Uzbekistan is to implement AI-based solutions for case handling and legal document retrieval and court decision processes. The research investigates the current legal framework and institutional setup as well as the digital systems and ethical and practical obstacles of AI implementation in courtrooms. The research assesses Uzbekistan's readiness to implement AI technology by analyzing global best practices and regional developments and its ability to protect fairness and transparency and due process. The article provides recommendations for a rights-based and cautious implementation of AI in Uzbekistan's judicial system.